1987
DOI: 10.1017/s0003356100018602
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal function in lambs treated with androgenic and oestrogenic growth stimulants

Abstract: Three experiments were carried out in which plasma cortisol concentrations were measured hourly in lambs treated with various anabolic steroids. In the first experiment, female lambs were implanted with trenbolone acetate (TBA) and plasma cortisol was measured for 24-h periods 4 weeks after implantation and 1 week after reimplantation. Plasma cortisol levels were unaltered 4 weeks after treatment, but were found to be significantly lower 1 week after retreatment. On this occasion, peak concentrations of cortis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…These authors in common with others (e.g. Sillence, Thomas, Anil, Redfern and Rodway (1987) using 40 mg implants) did not measure overall effects on body composition.…”
Section: Introductionmentioning
confidence: 93%
“…These authors in common with others (e.g. Sillence, Thomas, Anil, Redfern and Rodway (1987) using 40 mg implants) did not measure overall effects on body composition.…”
Section: Introductionmentioning
confidence: 93%
“…Previous work examining the effects of TBA and E 2 in female lambs suggests that the effects of implantation on cortisol concentrations may be a relatively short-term event. Sillence, Thomas [7], reported that plasma cortisol levels were lower but not significantly different in treated animals compared to non-implanted animals 4 wk after implantation. However, 1 wk after re-implantation with an androgenic and estrogenic growth stimulant, the implanted lambs had significantly lower plasma cortisol [7].…”
Section: Discussionmentioning
confidence: 95%
“…Sillence, Thomas [7], reported that plasma cortisol levels were lower but not significantly different in treated animals compared to non-implanted animals 4 wk after implantation. However, 1 wk after re-implantation with an androgenic and estrogenic growth stimulant, the implanted lambs had significantly lower plasma cortisol [7]. This is also consistent with loss of 21-and 11β-hydroxylase activity by androstenedione which occurred after only 1 h of exposure [18].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations